Defective Embodiment of Alien Hand Uncovers Altered Sensorimotor Integration in Schizophrenia. (31st May 2019) - Rossetti, Ileana; Romano, Daniele; Florio, Vincenzo; Doria, Stefania; Nisticò, Veronica; Conca, Andreas; Mencacci, Claudio; Maravita, Angelo
Abstract: The observation that people with schizophrenia misattribute the source of their own actions has led to the hypothesis that they suffer from altered sensorimotor processes underlying sense of agency. Furthermore, rubber hand studies suggest an abnormal experience of embodiment in schizophrenia. However, this latter finding is based on a procedure that elicits ownership sensations for a fake hand by visuo-tactile stimulation, leaving the agency subcomponent of embodiment relatively untouched. By using a visuo-motor version of the embodiment illusion able to actively elicit also sense of agency for an alien hand, we tested whether the putative sensorimotor deficits are also involved in altering embodiment sensations in schizophrenia. Subjective (questionnaire) and perceptual (forearm bisection performance) indexes of the embodiment illusion were collected. Differently from controls, both the explicit agency component and the implicit body metrics update were not modulated by the extent of visuo-motor congruency in participants with schizophrenia. We conclude that motor prediction and/or temporal binding window impairments may alter the feeling of embodiment and body representation in schizophrenia.